Improved Bounds for Acyclic Job Shop Scheduling - Feige, Uriel; Scheideler, Christian (Combinatorica)

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (SODA)

Compact, adaptive placement schemes for non-uniform requirements - Brinkmann, André; Salzwedel, Kay; Scheideler, Christian (SPAA)

Algorithms for fault-tolerant routing in circuit switched networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SPAA)

Models and Techniques for Communication in Dynamic Networks - Scheideler, Christian (STACS)

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Smoothed Motion Complexity - Damerow, Valentina; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian (ESA)

Anycasting in Adversarial Systems: Routing and Admission Control - Awerbuch, Baruch; Brinkmann, André; Scheideler, Christian (ICALP)

Peer-to-peer systems for prefix search - Awerbuch, Baruch; Scheideler, Christian (PODC)

Perfectly Balanced Allocation - Czumaj, Artur; Riley, Chris; Scheideler, Christian (RANDOM-APPROX)

On local algorithms for topology control and routing in ad hoc networks - Jia, Lujun; Rajaraman, Rajmohan; Scheideler, Christian (SPAA)

Information gathering in adversarial systems: lines and cycles - Kothapalli, Kishore; Scheideler, Christian (SPAA)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)

A Distributed Hash Table for Computational Grids - Riley, Chris; Scheideler, Christian (IPDPS)

Robust Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (IPTPS)

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IWIA)

The hyperring: a low-congestion deterministic data structure for distributed environments - Awerbuch, Baruch; Scheideler, Christian (SODA)

Consistent and compact data management in distributed storage systems - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Pagoda: a dynamic overlay network for routing, data management, and multicasting - Bhargava, Ankur; Kothapalli, Kishore; Riley, Chris; Scheideler, Christian; Thober, Mark (SPAA)

The effect of faults on network expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (SPAA)

Transparent Data Structures, or How to Make Search Trees Robust in a Distributed Environment - Korzeniowski, Miroslaw; Scheideler, Christian (ISPAN)

Supervised Peer-to-Peer Systems - Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Efficient Broadcasting and Gathering in Wireless Ad-Hoc Networks - Onus, Melih; W. Richa, Andrea; Kothapalli, Kishore; Scheideler, Christian (ISPAN)

Constant density spanners for wireless ad-hoc networks - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; W. Richa, Andrea (SPAA)

How to spread adversarial nodes?: rotate! - Scheideler, Christian (STOC)

Overlay networks for wireless ad hoc networks - Scheideler, Christian (IMA Workshop on Wireless Communications)

Improved bounds for the unsplittable flow problem - Kolman, Petr; Scheideler, Christian (J. Algorithms)

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IEEE Trans. Mob. Comput.)

Distributed coloring in O/spl tilde/(/spl radic/(log n)) bit rounds - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; Schindelhauer, Christian (IPDPS)

Robust Random Number Generation for Peer-to-Peer Systems - Awerbuch, Baruch; Scheideler, Christian (OPODIS)

Towards a scalable and robust DHT - Awerbuch, Baruch; Scheideler, Christian (SPAA)

The Effect of Faults on Network Expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (Theory Comput. Syst.)

Towards a paradigm for robust distributed algorithms and data structures - Scheideler, Christian (6th International HNI Symposium on New Trends in Parallel and Distributed Computing)

Algorithms for Fault-Tolerant Routing in Circuit-Switched Networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SIAM J. Discrete Math.)

Linearization: Locally Self-Stabilizing Sorting in Graphs - Onus, Melih; W. Richa, Andrea; Scheideler, Christian (Proceedings of the Nine Workshop on Algorithm Engineering and Experiments, ALENEX 2007, New Orleans, Louisiana, USA, January 6, 2007)

Towards Scalable and Robust Overlay Networks - Awerbuch, Baruch; Scheideler, Christian (6th International workshop on Peer-To-Peer Systems, IPTPS 2007, Bellevue, WA, USA, February 26-27, 2007)

A denial-of-service resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Proceedings of the Twenty-Sixth Annual ACM Symposium on Principles of Distributed Computing, PODC 2007, Portland, Oregon, USA, August 12-15, 2007)

A Denial-of-Service Resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Distributed Computing, 21st International Symposium, DISC 2007, Lemesos, Cyprus, September 24-26, 2007, Proceedings)

Distributed Computing in Sensor Systems, Third IEEE International Conference, DCOSS 2007, Santa Fe, NM, USA, June 18-20, 2007, Proceedings

SPAA 2007: Proceedings of the 19th Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Diego, California, USA, June 9-11, 2007

Overlay Networks for Peer-to-Peer Networks - W. Richa, Andrea; Scheideler, Christian (Handbook of Approximation Algorithms and Metaheuristics.)

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Can ISPs and P2P users cooperate for improved performance? - Aggarwal, Vinay; Feldmann, Anja; Scheideler, Christian (ACM Computer Commucation Review)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)

A Distributed and Oblivious Heap - Scheideler, Christian; Schmid, Stefan (Automata, Languages and Programming, 36th Internatilonal Colloquium, ICALP 2009, Rhodes, Greece, July 5-12, 2009, Proceedings, Part II)

A Self-stabilizing and Local Delaunay Graph Construction - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Algorithms and Computation, 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings)

A distributed polylogarithmic time algorithm for self-stabilizing skip graphs - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Proceedings of the 28th Annual ACM Symposium on Principles of Distributed Computing, PODC 2009, Calgary, Alberta, Canada, August 10-12, 2009)

A DoS-resilient information system for dynamic data management - Baumgart, Matthias; Scheideler, Christian; Schmid, Stefan (SPAA 2009: Proceedings of the 21st Annual ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, August 11-13, 2009)

Brief Announcement: On the Time Complexity of Distributed Topological Self-stabilization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Stabilization, Safety, and Security of Distributed Systems, 11th International Symposium, SSS 2009, Lyon, France, November 3-6, 2009. Proceedings)

Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Algorithmic Methods for Distributed Cooperative Systems, 06.09. - 11.09.2009)

Algorithmische Grundlagen verteilter Speichersysteme - Meyer auf der Heide, Friedhelm; Scheideler, Christian (Informatik Spektrum)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Towards jamming-resistant and competitive medium access in the SINR model - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 3rd ACM workshop on Wireless of the students, by the students, for the students, S3@MOBICOM 2011, Las Vegas, NV, USA, September 19 - 23, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)

Re-Chord: a self-stabilizing chord overlay network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (SPAA 2011: Proceedings of the 23rd Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Jose, CA, USA, June 4-6, 2011 (Co-located with FCRC 2011))

Hashed Patricia Trie: Efficient Longest Prefix Matching in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (WALCOM: Algorithms and Computation - 5th International Workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011. Proceedings)

Programming for Distributed Computing: From Physical to Logical Networks - Scheideler, Christian; Graffi, Kalman (Computer Science, The Hardware, Software and Heart of It)

Broadcasting - How Can I Quickly Disseminate Information? - Scheideler, Christian (Algorithms Unplugged)

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (28th International Symposium on Theoretical Aspects of Computer Science, STACS 2011, March 10-12, 2011, Dortmund, Germany)

Stabilizing consensus with the power of two choices - Doerr, Benjamin; Goldberg, Leslie Ann; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Proceedings of the 23rd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In the standard consensus problem there are n processes with possibly di®erent input values and the goal is to eventually reach a point at which all processes commit to exactly one of these values. We are studying a slight variant of the consensus problem called the stabilizing consensus problem [2]. In this problem, we do not require that each process commits to a ¯nal value at some point, but that eventually they arrive at a common, stable value without necessarily being aware of that. This should work irrespective of the states in which the processes are starting. Our main result is a simple randomized algorithm called median rule that, with high probability, just needs O(logmlog log n + log n) time and work per process to arrive at an almost stable consensus for any set of m legal values as long as an adversary can corrupt the states of at most p n processes at any time. Without adversarial involvement, just O(log n) time and work is needed for a stable consensus, with high probability. As a by-product, we obtain a simple distributed algorithm for approximating the median of n numbers in time O(logmlog log n + log n) under adversarial presence.

Self-Stabilizing DeBruijn Networks - Richa, Andrea W.; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
This paper presents a dynamic overlay network based on the De Bruijn graph which we call Linearized De Bruijn (LDB) network. The LDB network has the advantage that it has a guaranteed constant node degree and that the routing between any two nodes takes at most O(log n) hops with high probability. Also, we show that there is a simple local-control algorithm that can recover the LDB network from any network topology that is weakly connected.

Corona: A Stabilizing Deterministic Message-Passing Skip List - Nesterenko, Mikhail; Mohd, Rizal; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We present Corona, a deterministic self-stabilizing algorithm for skip list construction in structured overlay networks. Corona operates in the low-atomicity message-passing asynchronous system model. Corona requires constant process memory space for its operation and, therefore, scales well. We prove the general necessary conditions limiting the initial states from which a self-stabilizing structured overlay network in message-passing system can be constructed. The conditions require that initial state information has to form a weakly connected graph and it should only contain identiers that are present in the system. We formally describe Corona and rigorously prove that it stabilizes from an arbitrary initial state subject to the necessary conditions. We extend Corona to construct a skip graph.

Editorial for Algorithmic Aspects of Wireless Sensor Networks - Dolev, Shlomi; Scheideler, Christian (Theor. Comput. Sci.)

Selfish Distributed Optimization - Monien, Burkhard; Scheideler, Christian (Euro-Par 2012 Parallel Processing - 18th International Conference, Euro-Par 2012, Rhodes Island, Greece, August 27-31, 2012. Proceedings)

Towards higher-dimensional topological self-stabilization: A distributed algorithm for Delaunay graphs - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Theoretical Computer Science)
This article studies the construction of self-stabilizing topologies for distributed systems. While recent research has focused on chain topologies where nodes need to be linearized with respect to their identiers, we explore a natural and relevant 2-dimensional generalization. In particular, we present a local self-stabilizing algorithm DStab which is based on the concept of \local Delaunay graphs" and which forwards temporary edges in greedy fashion reminiscent of compass routing. DStab constructs a Delaunay graph from any initial connected topology and in a distributed manner in time O(n3) in the worst-case; if the initial network contains the Delaunay graph, the convergence time is only O(n) rounds. DStab also ensures that individual node joins and leaves aect a small part of the network only. Such self-stabilizing Delaunay networks have interesting applications and our construction gives insights into the necessary geometric reasoning that is required for higherdimensional linearization problems.Keywords: Distributed Algorithms, Topology Control, Social Networks

Tiara: A self-stabilizing deterministic skip list and skip graph - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Theoretical Computer Science)
We present Tiara — a self-stabilizing peer-to-peer network maintenance algorithm. Tiara is truly deterministic which allows it to achieve exact performance bounds. Tiara allows logarithmic searches and topology updates. It is based on a novel sparse 0-1 skip list. We then describe its extension to a ringed structure and to a skip-graph.Key words: Peer-to-peer networks, overlay networks, self-stabilization.

Stabilization, Safety, and Security of Distributed Systems
SSS is an international forum for researchers and practitioners in the design and development of distributed systems with self-properties: (classical) self-stabilizing, self-configuring, self-organizing, self-managing, self-repairing, self-healing, self-optimizing, self-adaptive, and self-protecting. Research in distributed systems is now at a crucialpoint in its evolution, marked by the importance of dynamic systems such as peer-to-peer networks, large-scale wireless sensor networks, mobile ad hoc networks, cloud computing, robotic networks, etc. Moreover, new applications such as grid and web services, banking and e-commerce, e-health and robotics, aerospace and avionics, automotive, industrial process control, etc. have joined the traditional applications of distributed systems. The theory of self-stabilization has been enriched in the last 30 years by high quality research contributions in the areas of algorithmic techniques, formal methodologies, model theoretic issues, and composition techniques. All these areas are essential to the understanding and maintenance of self-properties in fault-tolerant distributed systems.

Smoothed analysis of left-to-right maxima with applications - Damerow, Valentina; Manthey, Bodo; Meyer auf der Heide, Friedhelm; Räcke, Harald; Scheideler, Christian; Sohler, Christian; Tantau, Till (Transactions on Algorithms)
A left-to-right maximum in a sequence of n numbers s_1, …, s_n is a number that is strictly larger than all preceding numbers. In this article we present a smoothed analysis of the number of left-to-right maxima in the presence of additive random noise. We show that for every sequence of n numbers s_i ∈ [0,1] that are perturbed by uniform noise from the interval [-ε,ε], the expected number of left-to-right maxima is Θ(&sqrt;n/ε + log n) for ε>1/n. For Gaussian noise with standard deviation σ we obtain a bound of O((log3/2 n)/σ + log n).We apply our results to the analysis of the smoothed height of binary search trees and the smoothed number of comparisons in the quicksort algorithm and prove bounds of Θ(&sqrt;n/ε + log n) and Θ(n/ε+1&sqrt;n/ε + n log n), respectively, for uniform random noise from the interval [-ε,ε]. Our results can also be applied to bound the smoothed number of points on a convex hull of points in the two-dimensional plane and to smoothed motion complexity, a concept we describe in this article. We bound how often one needs to update a data structure storing the smallest axis-aligned box enclosing a set of points moving in d-dimensional space.

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

Competitive and fair throughput for co-existing networks under adversarial interference - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 31st Annual ACM SIGACT-SIGOPS Symposium on Principles and Distributed Computing (PODC))
This paper initiates the formal study of a fundamental problem: How to efficiently allocate a shared communication medium among a set of K co-existing networks in the presence of arbitrary external interference? While most literature on medium access focuses on how to share a medium among nodes, these approaches are often either not directly applicable to co-existing networks as they would violate the independence requirement, or they yield a low throughput if applied to multiple networks. We present the randomized medium access (MAC) protocol COMAC which guarantees that a given communication channel is shared fairly among competing and independent networks, and that the available bandwidth is used efficiently. These performance guarantees hold in the presence of arbitrary external interference or even under adversarial jamming. Concretely, we show that the co-existing networks can use a Ω(ε2 min{ε, 1/poly(K)})-fraction of the non-jammed time steps for successful message transmissions, where ε is the (arbitrarily distributed) fraction of time which is not jammed.

Brief Announcement: SplayNets - Towards Self-Adjusting Distributed Data Structures - Schmid, Stefan; Avin, Chen; Scheideler, Christian; Häupler, Bernhard; Lotker, Zvi (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
This paper initiates the study of self-adjusting distributed data structures for networks. In particular, we present SplayNets: a binary search tree based network that is self-adjusting to routing request.We derive entropy bounds on the amortized routing cost and show that our splaying algorithm has some interesting properties.

Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Approximate Duality of Multicommodity Multiroute Flows and Cuts: Single Source Case - Kolman, Petr; Scheideler, Christian (Proceedings of the 23th ACM SIAM Symposium on Discrete Algorithms (SODA))
Given an integer h, a graph G = (V;E) with arbitrary positive edge capacities and k pairs of vertices (s1; t1); (s2; t2); : : : ; (sk; tk), called terminals, an h-route cut is a set F µ E of edges such that after the removal of the edges in F no pair si ¡ ti is connected by h edge-disjoint paths (i.e., the connectivity of every si ¡ ti pair is at most h ¡ 1 in (V;E n F)). The h-route cut is a natural generalization of the classical cut problem for multicommodity °ows (take h = 1). The main result of this paper is an O(h722h log2 k)-approximation algorithm for the minimum h-route cut problem in the case that s1 = s2 = ¢ ¢ ¢ = sk, called the single source case. As a corollary of it we obtain an approximate duality theorem for multiroute multicom-modity °ows and cuts with a single source. This partially answers an open question posted in several previous papers dealing with cuts for multicommodity multiroute problems.

A Self-Stabilization Process for Small-World Networks - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Small-world networks have received significant attention because of their potential as models for the interaction networks of complex systems. Specifically, neither random networks nor regular lattices seem to be an adequate framework within which to study real-world complex systems such as chemical-reaction networks, neural networks, food webs, social networks, scientific-collaboration networks, and computer networks. Small-world networks provide some desired properties like an expected polylogarithmic distance between two processes in the network, which allows routing in polylogarithmic hops by simple greedy routing, and robustness against attacks or failures. By these properties, small-world networks are possible solutions for large overlay networks comparable to structured overlay networks like CAN, Pastry, Chord, which also provide polylogarithmic routing, but due to their uniform structure, structured overlay networks are more vulnerable to attacks or failures. In this paper we bring together a randomized process converging to a small-world network and a self-stabilization process so that a small-world network is formed out of any weakly connected initial state. To the best of our knowledge this is the first distributed self-stabilization process for building a small-world network.

Competitive throughput in multi-hop wireless networks despite adaptive jamming - W. Richa, Andréa; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing)

Corona: A stabilizing deterministic message-passing skip list - Mohd Nor, Rizal; Nesterenko, Mikhail; Scheideler, Christian (Theor. Comput. Sci.)

An Efficient and Fair MAC Protocol Robust to Reactive Interference - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (IEEE/ACM Trans. Netw.)

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (Theory of Computing Systems)
An elementary h-route ow, for an integer h 1, is a set of h edge- disjoint paths between a source and a sink, each path carrying a unit of ow, and an h-route ow is a non-negative linear combination of elementary h-routeows. An h-route cut is a set of edges whose removal decreases the maximum h-route ow between a given source-sink pair (or between every source-sink pair in the multicommodity setting) to zero. The main result of this paper is an approximate duality theorem for multicommodity h-route cuts and ows, for h 3: The size of a minimum h-route cut is at least f=h and at most O(log4 k f) where f is the size of the maximum h-routeow and k is the number of commodities. The main step towards the proof of this duality is the design and analysis of a polynomial-time approximation algorithm for the minimum h-route cut problem for h = 3 that has an approximation ratio of O(log4 k). Previously, polylogarithmic approximation was known only for h-route cuts for h 2. A key ingredient of our algorithm is a novel rounding technique that we call multilevel ball-growing. Though the proof of the duality relies on this algorithm, it is not a straightforward corollary of it as in the case of classical multicommodity ows and cuts. Similar results are shown also for the sparsest multiroute cut problem.

Locally Self-Adjusting Tree Networks - Avin, Chen; Häupler, Bernhard; Lotker, Zvi; Scheideler, Christian; Schmid, Stefan (Proceedings of the 27th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
This paper initiates the study of self-adjusting networks (or distributed data structures) whose topologies dynamically adapt to a communication pattern $σ$. We present a fully decentralized self-adjusting solution called SplayNet. A SplayNet is a distributed generalization of the classic splay tree concept. It ensures short paths (which can be found using local-greedy routing) between communication partners while minimizing topological rearrangements. We derive an upper bound for the amortized communication cost of a SplayNet based on empirical entropies of $σ$, and show that SplayNets have several interesting convergence properties. For instance, SplayNets features a provable online optimality under special requests scenarios. We also investigate the optimal static network and prove different lower bounds for the average communication cost based on graph cuts and on the empirical entropy of the communication pattern $σ$. From these lower bounds it follows, e.g., that SplayNets are optimal in scenarios where the requests follow a product distribution as well. Finally, this paper shows that in contrast to the Minimum Linear Arrangement problem which is generally NP-hard, the optimal static tree network can be computed in polynomial time for any guest graph, despite the exponentially large graph family. We complement our formal analysis with a small simulation study on a Facebook graph.

IRIS: A Robust Information System Against Insider DoS-Attacks - Eikel, Martina; Scheideler, Christian (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this work we present the first scalable distributed information system,i.e., a system with low storage overhead, that is provably robust againstDenial-of-Service (DoS) attacks by a current insider. We allow acurrent insider to have complete knowledge about the information systemand to have the power to block any ε-fraction of its serversby a DoS-attack, where ε can be chosen up to a constant. The taskof the system is to serve any collection of lookup requests with at most oneper non-blocked server in an efficient way despite this attack. Previously,scalable solutions were only known for DoS-attacks of past insiders, where apast insider only has complete knowledge about some past time pointt_0 of the information system. Scheideler et al. (DISC 2007, SPAA 2009) showedthat in this case it is possible to design an information system so that anyinformation that was inserted or last updated after t_0 is safe against a DoS-attack. But their constructions would not work at all for a current insider. The key idea behindour IRIS system is to make extensive use of coding. More precisely, we presenttwo alternative distributed coding strategies with an at most logarithmicstorage overhead that can handle up to a constant fraction of blocked servers.

CONE-DHT: A distributed self-stabilizing algorithm for a heterogeneous storage system - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 27th International Symposium on Distributed Computing (DISC))
We consider the problem of managing a dynamic heterogeneous storagesystem in a distributed way so that the amount of data assigned to a hostin that system is related to its capacity. Two central problems have to be solvedfor this: (1) organizing the hosts in an overlay network with low degree and diameterso that one can efficiently check the correct distribution of the data androute between any two hosts, and (2) distributing the data among the hosts so thatthe distribution respects the capacities of the hosts and can easily be adapted asthe set of hosts or their capacities change. We present distributed protocols forthese problems that are self-stabilizing and that do not need any global knowledgeabout the system such as the number of nodes or the overall capacity of thesystem. Prior to this work no solution was known satisfying these properties.

A Deterministic Worst-Case Message Complexity Optimal Solution for Resource Discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of 20th International Colloqium on Structural Information and Communication Complexity (SIROCCO))
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the add ress of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)) or bits (O(nlogn)) a node receives or sendscoincides with the lower bound, while ensuring only a linearruntime (O(n)) on the number of rounds.

RoBuSt: A Crash-Failure-Resistant Distributed Storage System - Scheideler, Christian; Setzer, Alexander; Eikel, Martina (Proceedings of the 18th International Conference on Principles of Distributed Systems (OPODIS))
In this work we present the first distributed storage system that is provably robust against crash failures issued by an adaptive adversary, i.e., for each batch of requests the adversary can decide based on the entire system state which servers will be unavailable for that batch of requests. Despite up to \gamma n^{1/\log\log n} crashed servers, with \gamma>0 constant and n denoting the number of servers, our system can correctly process any batch of lookup and write requests (with at most a polylogarithmic number of requests issued at each non-crashed server) in at most a polylogarithmic number of communication rounds, with at most polylogarithmic time and work at each server and only a logarithmic storage overhead. Our system is based on previous work by Eikel and Scheideler (SPAA 2013), who presented IRIS, a distributed information system that is provably robust against the same kind of crash failures. However, IRIS is only able to serve lookup requests. Handling both lookup and write requests has turned out to require major changes in the design of IRIS.

Re-Chord: A Self-stabilizing Chord Overlay Network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theory of Computing Systems)
The Chord peer-to-peer system is considered, together with CAN, Tapestry and Pastry, as one of the pioneering works on peer-to-peer distributed hash tables (DHT) that inspired a large volume of papers and projects on DHTs as well as peer-to-peer systems in general. Chord, in particular, has been studied thoroughly, and many variants of Chord have been presented that optimize various criteria. Also, several implementations of Chord are available on various platforms. Though Chord is known to be very efficient and scalable and it can handle churn quite well, no protocol is known yet that guarantees that Chord is self-stabilizing, i.e., the Chord network can be recovered from any initial state in which the network is still weakly connected. This is not too surprising since it is known that the Chord network is not locally checkable for its current topology. We present a slight extension of the Chord network, called Re-Chord (reactive Chord), that turns out to be locally checkable, and we present a self-stabilizing distributed protocol for it that can recover the Re-Chord network from any initial state, in which the n peers are weakly connected, in O(nlogn) communication rounds. We also show that our protocol allows a new peer to join or an old peer to leave an already stable Re-Chord network so that within O(logn)^2) communication rounds the Re-Chord network is stable again.

Principles of Robust Medium Access and an Application to Leader Election - Awerbuch, Baruch; Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Transactions on Algorithms)
This article studies the design of medium access control (MAC) protocols for wireless networks that are provably robust against arbitrary and unpredictable disruptions (e.g., due to unintentional external interference from co-existing networks or due to jamming). We consider a wireless network consisting of a set of n honest and reliable nodes within transmission (and interference) range of each other, and we model the external disruptions with a powerful adaptive adversary. This adversary may know the protocol and its entire history and can use this knowledge to jam the wireless channel at will at any time. It is allowed to jam a (1 − )-fraction of the timesteps, for an arbitrary constant > 0 unknown to the nodes. The nodes cannot distinguish between the adversarial jamming or a collision of two or more messages that are sent at the same time. We demonstrate, for the first time, that there is a local-control MAC protocol requiring only very limited knowledge about the adversary and the network that achieves a constant (asymptotically optimal) throughput for the nonjammed time periods under any of the aforementioned adversarial strategies. The derived principles are also useful to build robust applications on top of the MAC layer, and we present an exemplary study for leader election, one of the most fundamental tasks in distributed computing.